Los esclavos en la documentación notarial de Jerez de la Frontera (1392-1550) / The Slaves in the Notarial Documentation of Jerez de la Frontera (1392-1550). - Abril Fuertes, José María; Mingorance Ruiz, José A. (Historia. Instituciones. Documentos, 2017)
RESUMEN: Entre los estudios sobre los grupos marginales de la sociedad del Antiguo Régimen sobresalen los referidos a la esclavitud. Jerez de la Frontera por su potencial demográfico y económico debía ser una ciudad con una gran cantidad de esclavos en los momentos finales del Medievo y comienzos de la Modernidad, desde que se conservan registros notariales (1392) hasta mediado el siglo XVI. El presente artículo se centra en el análisis de la documentación notarial en la que hemos hallado noticias referidas a dicho colectivo, procedentes del Archivo de Protocolos Notariales de la ciudad. Ofrecemos una variada casuística recogida en dichos contratos. ABSTRACT: Among the studies about marginal groups of the Ancient Regime society the ones which stand out are those that concern slavery. Due to its demographic and economic potential, Jerez de la Frontera must have had numerous slaves in the final moments of the Medieval Ages and the beginnings of the Modern Age, from the first preserved notaries´ documentation (1392) until the first half of the 16th century. The article focuses on the analysis of the notaries’ documentation from the Notaries’ Protocols Archives of the city, where we have found news about the aforementioned social group. We will offer a diverse range of cases from those contracts.